2002
DOI: 10.1523/jneurosci.22-05-01858.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Aβ and Memory in the Tg2576 Mouse Model of Alzheimer's Disease

Abstract: Transgenic mice expressing mutant amyloid precursor proteins (APPs) have provided important new information about the pathogenesis of Alzheimer's disease (AD) histopathology. However, the molecular basis of memory loss in these mice is poorly understood. One of the major impediments has been the difficulty of distinguishing between age-dependent and ageindependent behavioral changes. To address this issue we studied in parallel two lines of APP transgenic mice expressing comparable levels of mutant and wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
552
6
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 658 publications
(601 citation statements)
references
References 50 publications
(75 reference statements)
42
552
6
1
Order By: Relevance
“…These mice develop early synaptic deficits 12 and several neuropathological features at older age, including amyloid plaques and dystrophic neurites 13 . Although Tg2576 mice lack neurofibrillary tangles and significant neuronal loss 14 , there is strong evidence that accumulation of the amyloid-β (Aβ) peptide, derived via APP proteolysis, is responsible for age-related memory decline in this model [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mice develop early synaptic deficits 12 and several neuropathological features at older age, including amyloid plaques and dystrophic neurites 13 . Although Tg2576 mice lack neurofibrillary tangles and significant neuronal loss 14 , there is strong evidence that accumulation of the amyloid-β (Aβ) peptide, derived via APP proteolysis, is responsible for age-related memory decline in this model [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…These mice develop early synaptic deficits 12 and several neuropathological features at older age, including amyloid plaques and dystrophic neurites 13 . Although Tg2576 mice lack neurofibrillary tangles and significant neuronal loss 14 , there is strong evidence that accumulation of the amyloid-β (Aβ) peptide, derived via APP proteolysis, is responsible for age-related memory decline in this model [15][16][17] .By means of several experimental approaches, we demonstrate an increase of caspase-3 activity in Tg2576 hippocampal synapses at 3 months of age, much earlier than amyloid plaque deposition is detectable 11 . We report that this enhanced local caspase-3 activity leads to a permanent activation of calcineurin which causes, in turn, AMPA receptor (AMPAR) GluR1 subunit dephosphorylation and its removal from the post-synaptic sites.…”
mentioning
confidence: 82%
“…However, it has been reported that there does not seem to be a direct, simple correlation between levels of insoluble (i.e., aggregated) A␤ and cognitive deficits observed in transgenic mice that express a mutant form of human APP. It appears that soluble forms of A␤ correlate better with the cognitive declines observed in these mice (Westerman et al, 2002).…”
Section: Steroid Hormones and Neuronal Nachrsmentioning
confidence: 91%
“…In summary, the evidence that oligomeric Aβ42 is the most toxic species of Aβ is convincing. Studies strongly support the following: 1) all else being equal, enriched oligomeric preparations of Aβ42 appear to be the most toxic species [38,39]; 2) oligomeric species of Aβ42 can inhibit long term potentiation (LTP) and lead to synaptic dysfunction [48,49]; 3) memory loss occurs prior to extensive deposition of fibrillar Aβ42 in transgenic mice and can be reversed by targeting soluble species of Aβ42 [50,51,52,53]; and 4) oligomeric Aβ42 species exist in AD brain [54]. However, it is important to appreciate that the removal or reduction of the soluble, toxic oligomeric forms of Aβ42 from brain parenchyma will require the concomitant reduction and removal of the insoluble (fibrillar) Aβ42 pool as well.…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 94%
“…In Tg2576 mice, no obvious correspondence between memory and insoluble Aβ levels was apparent [53]. Furthermore, passive immunization studies of this same Tg2576 strain of mice showed that memory deficits and disruption of LTP can be reversed without affecting the levels of soluble or insoluble Aβ, suggesting "neutralization" of soluble Aβ by antibodies may be sufficient to aid in cognitive improvement [51,52].…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 97%